Psychosocial mediators of change in physical activity in the Welsh national exercise referral scheme: secondary analysis of a randomised controlled trial - Littlecott, Hannah J (BioMed Central, 2014)
OBJECTIVE: While an increasing number of randomised controlled trials report impacts of exercise referral schemes (ERS) on physical activity, few have investigated the mechanisms through which increases in physical activity are produced. This study examines whether a National Exercise Referral Scheme (NERS) in Wales is associated with improvements in autonomous motivation, self-efficacy and social support, and whether change in physical activity is mediated by change in these psychosocial processes. METHODS: A pragmatic randomised controlled trial of NERS across 12 LHBs in Wales. Questionnaires measured demographic data and physical activity at baseline. Participants (N = 2160) with depression, anxiety or CHD risk factors were referred by health professionals and randomly assigned to control or intervention. At six months psychological process measures were collected by questionnaire. At 12 months physical activity was assessed by 7 Day PAR telephone interview. Regressions tested intervention effects on psychosocial variables, physical activity before and after adjusting for mediators and socio demographic patterning. RESULTS: Significant intervention effects were found for autonomous motivation and social support for exercise at 6 months. No intervention effect was observed for self-efficacy. The data are consistent with a hypothesis of partial mediation of the intervention effect by autonomous motivation. Analysis of moderators showed significant improvements in relative autonomy in all subgroups. The greatest improvements in autonomous motivation were observed among patients who were least active at baseline. DISCUSSION: The present study offered key insights into psychosocial processes of change in an exercise referral scheme, with effects on physical activity mediated by autonomous motivation. Findings support the use of self-determination theory as a framework for ERS. Further research is required to explain socio-demographic patterning in responses to ERS, with changes in motivation occurring among all sub-groups of participants, though not always leading to higher adherence or behavioural change. This highlights the importance of socio-ecological approaches to developing and evaluating behaviour change interventions, which consider factors beyond the individual, including conditions in which improved motivation does or does not produce behavioural change. TRIAL REGISTER NUMBER: ISRCTN47680448